Perkembangan Banjar Belaluan Sadmerta di Kota Denpasar tahun 1957-2017 - Putra Udayana, Anak Agung Ngurah; Ardhana, I Ketut (Humanis; Vol 23 No 2 (2019), 2019)
This research choose the development of banjar Belaluan Sadmerta in Denpasar as its topic. There are two questions asked in this research which are, 1)What are factors behind establishment of banjar Belaluan Sadmerta, and 2) How’s the development of banjar Belaluan Sadmerta in socio-cultural, religion, economy and politic in Denpasar within 1957-2017. This research used social history method by Kuntowijoyo, which is used to find out level of development. This research used Historical Theory by Ida Bagus Sidemen which explained, 1) Historical Explanation, 2) Historical Obje c tivity , 3)H istorical Determinism . The theory used as basis in exploring and reconstructing data in this research. Development as concept, defined the development of banjar Belaluan Sadmerta to be perfect in both abstract and concrete forms. In this way, this research was able to produce conclusions from each research questions which then used as conclusion that the establishment of banjar Belaluan Sadmerta was inseparable from the dominant role of a sekaa or group and important society’s figures in its development. Regional autonomy is also an opportunity for the societies to make banjar Belaluan Sadmerta as a place for societies to carry out daily activities.